Velocidade da bola no chute no futsal: comparação entre garotos com diferentes níveis de desempenho e correlação de variáveis preditoras do desempenho - Andrade, Vitor Luiz De; Vieira, Luiz Henrique Palucci; Bedo, Bruno Luiz De Souza; Macari, Reinaldo; Mariano, Fábio Pamplona; Noda, Cesar Tadashi; Santiago, Paulo Roberto Pereira (Escola de Educação Física e Esporte da Universidade de São Paulo, 2015)
AbstractThe aim of this study was to compare and verify the possible correlations between ball velocity with foot velocity, knee angle and length of last stride between practitioners and non-practitioners of futsal game. Fourteen young males with aged between 13 and 15 years old divided into two groups: practitioners (G1) and non-practitioners (G2), according with the time of futsal structured practice. For the kinematic analysis we had used two cameras at a sampling frequency of 120 Hz, fixed laterally to the movement performed in order to focus the markers in the limb of kick. Each participant has performed ten kicks simulating a kick of ten meters in futsal. Three-dimensional data of the lower limb of kick were obtained in DVIDEOW software and treated in Matlab environment in order to obtain the variables of interest: ball velocity (VELBALL), foot velocity (VELFOOT), knee angle (ANGKNEE) and length of last stride (LLS). Statistically all data displayed higher levels in G1 compared to G2. In addition, no significant differences were found between trials in each group (p < 0.05). In G1 a multiple regression analysis revealed only influence on VELBALL 17% caused by LLS. Moreover, in G2 any variable have influenced VELBALL. However, we conclude that the variables are different between practitioners and non-practitioners of futsal game with aged between 13 and 15 years old, and the variable VELBALL could be little influenced by the LLS in this age band. Thus, we suggested that coaches maintain focus on development and monitoring this characteristic of movement, especially in novices, in order to identify players with different levels of performance of kicking in a futsal context.

ResumoO estudo objetivou comparar e verificar as possíveis correlações entre a velocidade da bola com a velocidade do pé, ângulo relativo do joelho e comprimento do último passo durante o chute entre garotos Praticantes e Não Praticantes do futsal. Participaram do estudo 14 garotos com idade entre 13 e 15 anos divididos em dois grupos, Praticantes (G1) e Não Praticantes (G2) de acordo com seu tempo de prática estruturada semanal na modalidade. Para a análise cinemática duas câmeras ajustadas a uma frequência de 120 Hz, foram fixadas lateralmente ao movimento realizado e focalizando os marcadores fixados no membro inferior do chute. Cada participante executou 10 chutes simulando uma cobrança de tiro livre no futsal. Os dados tridimensionais do membro inferior de chute foram obtidos pelo software DVIDEOW e tratados em ambiente Matlab, para obtenção das variáveis cinemáticas de interesse: velocidade da bola (VELBOLA), velocidade do pé (VELPÉ), ângulo de joelho (ANGJOELHO) e comprimento do último passo (CP). Todas as variáveis exibiram índices estatisticamente maiores em G1 se comparado a G2 e, além disso, não foram encontradas diferenças intertentativas na tarefa (p < 0,05). No G1 uma análise de regressão múltipla somente revelou influência na VELBOLA em 17% causada pelo CP. Além disso, no G2 nenhuma variável influenciou na VELBOLA. Pode-se concluir que as variáveis estudadas são diferentes entre praticantes e não praticantes de futsal com idade entre 13 - 15, e que a VELBOLA pode ser ligeiramente influenciada pelo CP nesta faixa etária. Recomenda-se que treinadores monitorem periodicamente o desenvolvimento desta característica do movimento, principalmente em jogadores novatos, como forma de identificar jogadores com diferentes níveis de desempenho no chute em um contexto de futsal.
Ball velocity on the kick in futsal: comparison between youth with different performance levels and correlation of the predictive variables of performance
Keywords: Biomechanics; Kinematics; Motor skills; Futsal; Biomecânica; Cinemática; Habilidades motoras; Futsal